Inevitability of Multiculturalism: A Critical Study of Anita Desai’s Voices in the City - THARANI, K.; VIJAYKUMARI, N. (International Journal of Psychosocial Rehabilitation, 2020)
This paper attempts to make a conscientious examination on multicultural conflicts in Anita Desai’s Voices in the City. It unfolds the events, the cultural, social, political happenings, occasions, which manifest multicultural conflicts in the Indian as well as Western contexts. It also highlights the Indian conditions that, it is a land of multi-culture, multi-religion, multi-ethnical, multi-lingual, multi-customs and traditions, there, it is rightly proved what is multiculturalism. In her novel, Anita Desai deals with immigrants’ problems, the Indians in western countries with nostalgic sense and a few Europeans in India suffering a lot unable to adjust. Her characters mostly find themselves rootless and are unable to stand firmly in any one culture. It also dealt with concepts of multiculture and multiculturalism, the causes of migration, the problems of immigrants and the diasporic and expatriates problems, which is an enigma of the global era.